Frequency and associated factors of mental health problems in COVID-19 vaccinated workers at a peruvian public hospital: Frecuencia y factores asociados a problemas de salud mental en trabajadores vacunados contra el COVID19 de un hospital público peruano - Collantes-Schmidt, José Raúl (2024)
Introduction: The pandemic increased stress and underdiagnosed mental health issues in the workplace.Objetive: To determine the frequency of mental health problems and their associated factors among vaccinated workers at the Dos de Mayo National Hospital (HNDM).Methods: A cross-sectional analytical study was conducted using secondary data from a mental health survey carried out by the HNDM Mental Health Service in October 2021. The Self-Reporting Questionnaire (SRQ) was administered to all HNDM workers who had received the full vaccination scheme. Statistical analysis included chi-square tests and logistic regression to identify associated factors.Results: Of 2109 workers, 2.7% presented mental health problems, with a higher prevalence in women (3.4%) compared to men (1.5%), and more frequent in the age groups 18-29 years (4.8%) and 50-59 years (4%). Divorced/separated individuals (7%) had a higher prevalence compared to single (2.8%) or married (2%) individuals. Multivariate analysis indicated a positive association with women (ORa: 2.30; 95% CI: 1.22-4.84) and divorced/separated individuals (ORa: 3.00; 95% CI: 1.12-7.25) compared to married/cohabiting individuals. There was a negative association in the 30-39 years (ORa: 0.43, 95% CI: 0.19-0.96) and 40-49 years (ORa: 0.30, 95% CI: 0.11-0.81) age groups compared to 18-29 years. No significant associations were found for other variables.Conclusion: One in forty HNDM workers presented mental health problems, with higher risks observed among women, younger and older age groups, and divorced/separated individuals. Improved screening and support for early intervention are recommended.